Communication Strategies in French Language Learning among Non-Native Adult Speakers / Hazlina Abdul Halim..[etc al.] - Abdul Halim, Hazlina; Abdul Halim, Normaliza; Mamat, Roslina (Universiti Teknologi MARA Cawangan Kedah, 2013)
This exploratory study aimed to determine and categorize the type of Malaysian non-native speakers’ communication strategies (CS) in learning French with regard to speaking skills. The study, which was based on Dornyei & Scott’s (1997) model of communication strategy, utilized both a qualitative and a simple quantitative method of data collection. The subjects consisted of 2nd and 3rd year foreign language students from various programs at Universiti Putra Malaysia (UPM). A total of 10 Malaysian students in the French language course participated in this study. The main instruments used were a speaking task prompt, an observation checklist, and an audio recording. The overall findings based on the observations and transcription of the audio recordings indicated that among the most frequently used communication strategies were the use of literal translation (26.4%), the use of all-purpose words (18.4%), topic abandonment (12.8%) and foreignizing from English (8.8%). The findings have resulted in a framework for foreign language instruction and materials design. It also suggested that further intensive research should be conducted to design and develop a communication strategies instruction framework which would lead to the development of a comprehensive framework for the incorporation of communication strategy in foreign language learning instruction, materials and tasks for Malaysian learners.